Hubungan Tingkat Pengetahuan dan Ketepatan Penggunaan Obat Simvasatatin Pada Pasien Hiperkolesterolemia di Rumah Sakit Advent Medan - Andre Budi; Rike Monika Sijabat (Journal of Pharmaceutical and Sciences, 2023)
Hypercholesterolemia is a condition when there is a disturbance in the body which is characterized by an increase in blood cholesterol levels exceeding 240 mg/dl. Pharmacological therapy that can be used to lower cholesterol levels is statin class drugs. Simvastatin is a hypercholesterolemia drug that is often used as a first-line drug compared to other statin class drugs. Based on the research that has been done, the results of the correlation test were obtained with a value 0,553, which means that there is a strong correlation between the level of knowledge and the accuracy of using simvastatin.